INFLUNCE OF HEALTH EDUCATION USING AUDIOVISUAL FOOT EXERCISES OF KNOWLEDGE AND SPECIALIZATION IN PATIENTS WITH DIABETES MELLITUS AT RSUD dr. DRADJAT PRAWIRANEGARA SERANG - Yusnita, Erny; Asra, Asra; Sulesmi, Siti; Lusiani, Milawati (AGUSPATI Research Institute, 2020)
Diabetes mellitus (DM) is the presence of insulin deficiency, reduced insulin or both of which cause metabolic disorder characterized by hiperglicemia, can cause diabetic neuropathy, foot ulcers, retinopathy, nephropathy, and vascular disorders. One way to prevent injury and improve blood circulation with foot exercises health education. But there are still many people with diabetes mellitus who do not know and do foot gymnastics.. The objective of this reseach is how to know influence of health education using audio-visual foot exercises of knowledge and specialization in DM patients in RSUD dr. Dradjat Prawiranegara Serang. This is quasi experimental reaseach with One Group Pre and Post Test Design that was done at the medical care room in RSUD Dr. Dradjat Prawiranegara Serang from Desember 2017 to February 2018 with 33 samples. Data instruments were quesionery. Univariate analysis (mean of knowledge and specialization) and bivariate analysis with computerized T dependen test. Result shows significant influenced of mean knowledge and specialization between before and after foot exercises (p= 0,00; p= 0,000). Based on the results of this research is expected to the hospital, especially the health promotion department to develop promotional activities using various methods and media so as to increase interest and motivation for people with DM. Also expected to incorporate foot exercise in DM patients into one of the health promotional activities in RSUD dr. Dradjat Prawiranegara Serang.